The "Secret" in Secretions: Methodological Considerations in Deciphering Primate Olfactory Communication. Issue 7 (22nd March 2013) - DREA, CHRISTINE M.; BOULET, MARYLÈNE; DELBARCO‐TRILLO, JAVIER; GREENE, LYDIA K.; SACHA, CAITLIN R.; GOODWIN, THOMAS E.; DUBAY, GEORGE R.; Higham, James P.; Semple, Stuart
Abstract Olfactory communication in primates is gaining recognition; however, studies on the production and perception of primate scent signals are still scant. In general, there are five tasks to be accomplished when deciphering the chemical signals contained in excretions and secretions: (1) obtaining the appropriate samples; (2) extracting the target organic compounds from the biological matrix; (3) separating the extracted compounds from one another (by gas chromatography, GC or liquid chromatography, LC); (4) identifying the compounds (by mass spectrometry, MS and associated procedures); and (5) revealing biologically meaningful patterns in the data. Ultimately, because some of the compounds identified in odorants may not be relevant, associated steps in understanding signal function involve verifying the perception or biological activity of putative semiochemicals via (6) behavioral bioassays or (7) receptor response studies. This review will focus on the chemical analyses and behavioral bioassays of volatile, primate scent signals. Throughout, we highlight the potential pitfalls of working with highly complex, chemical matrices and suggest ways for minimizing problems. A recurring theme in this review is that multiple approaches and instrumentation are required to characterize the full range of information contained in the complex mixtures that typify primate or, indeed, many vertebrate olfactory cues. Only by integrating studies of signal production with those verifying signal perception will we better understand the function of olfactory communication. Am. J. Primatol. 75:621–642, 2013. © 2013 Wiley Periodicals, Inc.